As time goes by: SMA neuromodulation and time perception while watching moving images with different editing styles. A tDCS study - Cancer, Alice; Balzarotti, Stefania; Antonietti, Alessandro; D’Aloia, Adriano; Eugeni, Ruggero (Frontiers in Human Neuroscience, 2025)
Within the framework of a “neurofilmological” approach – which integrates film studies, cognitive psychology, and neuroscience – the present study explored how cinematographic editing influences the viewer’s perception of time. Previous behavioral research has shown that editing density affects temporal judgments. To investigate the neural mechanisms underlying this relationship, we examined the role of motor system activity, specifically the supplementary motor area (SMA), in time perception when individuals are exposed to moving images with different cinematographic editing styles. Forty-eight university students were assigned to one of three tDCS conditions (anodal, cathodal, or sham). They viewed nine silent video clips with different editing styles (master shot, slow-paced, fast-paced) that were specifically created for research. The participants rated perceived duration, time passage, action speed, and emotional engagement, while tDCS was applied for 20 min targeting the SMA. The results revealed that SMA excitability modulation affected duration estimates, time passage, and action speed judgments by interacting with the editing style of the clips. These findings highlight the importance of the SMA in modulating time perception during film viewing. Furthermore, they provide valuable insights into the neural mechanisms that shape the viewer’s perception of film time as an integral part of experiencing movement in cinema.